Comparison of the effects of remifentanil-based general anesthesia and popliteal nerve block on postoperative pain and hemodynamic stability in diabetic patients undergoing distal foot amputation: A retrospective observational study. Issue 29 (July 2016) - Kim, Na Young; Lee, Ki-Young; Bai, Sun Joon; Hong, Jung Hwa; Lee, Jinwoo; Park, Jong Min; Kim, Shin Hyung
Abstract : Abstract: Diabetic foot ulcer is the most common cause of diabetes-associated nontraumatic lower extremity amputation. Most patients who undergo lower extremity amputation for a diabetic foot have had diabetes for a long time and suffer from multiorgan disorder; thus, it can be a challenge to ensure sufficient anesthetic and analgesic effects while maintaining stable hemodynamics. Recently, peripheral nerve block has gained popularity owing to its attenuating effects of systemic concerns. This retrospective observational study aimed to compare the effects of remifentanil-based general anesthesia (GEA) and popliteal nerve block (PNB) on postoperative pain and hemodynamic stability in diabetic patients undergoing distal foot amputation. A total of 59 consecutive patients with a diabetic foot who underwent distal foot amputation between January 2012 and May 2014 were retrospectively reviewed. Patients received remifentanil-based GEA (GEA group, n = 32) or PNB (PNB group, n = 27). The primary outcomes were to evaluate postoperative analgesic effects and perioperative hemodynamics. Also, postoperative pulmonary complications and 6-month mortality were assessed as secondary outcomes. Significant differences in pain scores using numeric rating scale were observed between the groups in a linear mixed model analysis ( P Group×Time = 0.044). Even after post hoc analysis with the Bonferroni correction, the numeric rating scale scores were significantly lower in the PNB group. Furthermore, patients in the PNB group required less pethidine during the first 6 hours after surgery (27 ± 28 vs 9 ± 18 mg; P = 0.013). The GEA group had a lower mean blood pressure (Bonferroni-corrected P < 0.01), despite receiving more ephedrine ( P < 0.001). Significantly more patients in the GEA group suffered from postoperative pneumonia and required the management in intensive care unit ( P = 0.030 and 0.038, respectively). However, the groups did not differ in terms of 6-month mortality. This study demonstrated that compared with remifentanil-based GEA, PNB might be a favorable option for diabetic patients undergoing distal foot amputation, despite the lack of significant mortality benefits, as PNB was associated with improved postoperative analgesia, hemodynamic stability, and a low incidence of pulmonary complications during the immediate postoperative period, especially in high-risk patients.